i-AqadQuest - Punding, Azlan Yusof; Henry, Hilda; Ayum, Flora; Richardson, Elizabeth; Henry, Jeslyna Jeliah (2025)
The Islamic banking sector is experiencing rapid growth and is projected to reach a market value of USD 7.7 trillion by 2033. This expansion highlights the urgent need for accessible educational tools to improve understanding of complex Shariah-compliant financial contracts. Traditional methods, such as textbooks and lectures, often lack the engagement and practicality needed to equip learners effectively. To address this gap, i-AqadQuest was developed as an interactive, gamified learning platform designed to simplify Islamic banking concepts for students, professionals, and the public. Built on the ZEP Quiz platform, it transforms learning into a game-based experience using attractive visuals, customizable avatars, interactive quizzes, and real-time feedback. Users engage in a virtual environment, answering questions to progress and receiving immediate corrections that strengthen understanding. The platform encourages active participation and enhances retention of knowledge while fostering a deeper comprehension of Islamic banking. Features such as leaderboards help create a motivating, competitive learning environment. Furthermore, i-AqadQuest is device-friendly, free to access, and requires no registration, making it ideal for individual and classroom use. Beyond improving financial literacy, i-AqadQuest offers a flexible, self-paced learning solution for professionals seeking to stay updated with the industry developments. It holds strong commercial potential for educational institutions, training programs, and community outreach. Future developments may include mobile app integration, expanded content, and additional features to further improve accessibility and enrich the user experience.